The Investigation of the Cardiovascular and Sudomotor Autonomic Nervous System—A Review - Ziemssen, Tjalf; Siepmann, Timo (Frontiers in Neurology, 2019)
The autonomic nervous system is extremely diffuse with its pathways permeating all organ systems. So the autonomic nervous system with its central part and sympathetic and parasympathetic efferent systems is involved with virtually all diseases. The cardiovascular autonomic nervous system is the most frequently examined system because its biosignals like heart frequency and blood pressure can be easily recorded and important diagnostic and prognostic information can be drawn from their analysis. The clinical approach before any special autonomic testing begins with a detailed history and clinical examination. Subjects should be adequately prepared before the autonomic testing to minimize the effects of confounding variables. As no single test is sufficiently reliable, it is recommended to use a battery of different tests to evaluate parasympathetic and sympathetic cardiovascular function. A reasonable battery of tests involves the heart rate response to deep breathing as well as the heart rate and blood pressure response to the valsalva maneuver, tilt or pressor stimuli. More special tests of the cardiovascular autonomic nervous system are carotid sinus massage, assessment of baroreceptor reflex function, pharmacological tests or cardiac and regional hemodynamic measurements. Although less widely established, sudomotor tests pose a useful supplement to cardiovascular autonomic assessment as impaired neurogenic sweating belongs to the earliest clinical signs of various autonomic neuropathies as well as neurodegenerative disorders and significantly reduces quality of life. Techniques to measure functional integrity of sudomotor nerves include the quantitative sudomotor axon reflex sweat test, analysis of the sympathetic skin response as well as the thermoregulatory sweat test. In addition to these rather established techniques more recent developments have been introduced to reduce technical demands and interindividual variability such as the quantitative direct and indirect axon reflex testing or sudoscan. However, diagnostic accuracy of these tests remains to be determined. We reviewed the current literature on currently available autonomic cardiovascular and sudomotor tests with a focus on their physiological and technical mechanisms as well as their diagnostic value in the scientific and clinical setting.